1992
DOI: 10.1161/01.cir.86.3.926
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal left ventricular intracavitary flow acceleration in patients undergoing aortic valve replacement for aortic stenosis. A marker for high postoperative morbidity and mortality.

Abstract: Background. We examined the clinical and echocardiographic characteristics of patients undergoing aortic valve replacement for aortic stenosis whose continuous wave Doppler studies showed abnormal intracavitary flow acceleration.Methods and Resuls. The clinical and Doppler echocardiographic records of 53 consecutive patients undergoing aortic valve replacement for aortic stenosis were reviewed. Doppler echocardiography was performed at a mean of 6.6 days (range, 0-22 days) after surgery. Thirteen patients (gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(91 citation statements)
references
References 36 publications
0
91
0
Order By: Relevance
“…78 -80 Another problem that is particularly common in elderly patients, especially women, is an excessive or inappropriate degree of hypertrophy; wall thickness is greater than necessary to counterbalance the high intracavitary pressures. [81][82][83][84] As a result, systolic wall stress is low and ejection fraction is high; such inappropriate LV hypertrophy has been associated with high perioperative morbidity and mortality. 81,83 …”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…78 -80 Another problem that is particularly common in elderly patients, especially women, is an excessive or inappropriate degree of hypertrophy; wall thickness is greater than necessary to counterbalance the high intracavitary pressures. [81][82][83][84] As a result, systolic wall stress is low and ejection fraction is high; such inappropriate LV hypertrophy has been associated with high perioperative morbidity and mortality. 81,83 …”
Section: Pathophysiologymentioning
confidence: 99%
“…Likewise, excessive or inappropriate hypertrophy associated with valvular stenosis can be a marker for perioperative morbidity and mortality. 81,83 Preoperative recognition of elderly patients with marked LV hypertrophy followed by appropriate perioperative management can reduce this morbidity and mortality substantially. There is no perfect method for weighing all of the relevant factors and identifying specifically high-and low-risk elderly patients, but this risk can be estimated well in individual patients.…”
Section: Special Considerations In the Elderlymentioning
confidence: 99%
“…[1][2][3] Although SAM with an associated LVOT gradient sometimes occurs after AVR for AS, it is rarely related to clinical symptoms. Several reports have demonstrated that LVOT obstruction, with MR resulting from SAM after AVR, leads to hemodynamic collapse.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] However, such patients rarely present with clinical symptoms. Therefore, therapy for the reduction of left ventricular pressure gradient associated with SAM has not been established.…”
Section: S Ystolic Anterior Motion (Sam) Of the Mitral Valve Aftermentioning
confidence: 99%
“…This view, accepted for the past 40 years 3 and perhaps counterintuitively expected to mitigate the effects of LV pressure overload on cardiovascular morbidity and mortality, has begun to be challenged by new clinical data, suggesting that moderate or severe LVH may be associated with adverse outcomes in AS 4,5 and that inappropriately increased LV mass, found in 17% of patients with mild to moderate AS 6 and in 67% of patients with asymptomatic severe AS, was associated with a 4.5-fold increased risk of cardiovascular events. 7 Conversely, the absence of hypertrophy in one third of the patients with severe AS seems to have no adverse effects on systolic function or survival.…”
Section: See Article By Gerdts Et Almentioning
confidence: 99%